ETHNOMATHEMATICS THOUGHT AND ITS INFLUENCE IN MATHEMATICAL LEARNING - Andi Saparuddin Nur; Kartono Kartono; Zaenuri Zaenuri; S B Waluya; Rochmad Rochmad (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Mathematics is a symbol of rationality and the highest intellectual achievements of human civilization. Mathematics has always been seen as abstract and formal knowledge. However, in the last few decades, the idea has emerged that mathematics is a knowledge that develops in human cultural activities. The concept of mathematics in culture is widely known as ethnomathematics. This paper aims to briefly describe the history, criticism, and challenges of ethnomathematics, the thoughts of ethnomathematics experts, and their influence in learning mathematics today. The development of ethnomathematics gave rise to a field of study covering aspects of anthropology and the history of mathematics, non-formal mathematics practice, traditional mathematics, and multicultural learning. Various research results indicate that ethnomathematics contributes to improving school mathematics. Although culture has an important role in learning mathematics, to integrate it requires comprehensive efforts to overcome various obstacles. Teachers need to improve competencies related to understanding local culture to maximize the transformation of ethnomathematics learning in the classroom.